Culinary students' career intention in the hospitality industry: the importance of the work environment during practical training / Siti Nurhanifah Sulong ... [et al.] - Sulong, Siti Nurhanifah; Mohamad, Norhaya Hanum; Ahmad Shariff, Siti Nor Fadillah; Arifin, Aniza; Abdul Manap, Malisa Sahila (Universiti Teknologi MARA, Perlis, 2021)
The main objective of this study is to examine the importance of the work environment during students' practical training toward students' career intention in the hospitality industry. This study uses a quantitative method through the distribution of self-administrated questionnaire surveys. Convenience sampling was selected from 159 culinary arts students at UiTM Cawangan Terengganu Kampus Dungun (UiTMCTKD). This sampling design was selected due to its high efficiency. The students had completed their practical training 2 weeks before data collection. Descriptive and inferential analyses were used to interpret the data. Findings from this study revealed that the work environment influences students' career intention toward pursuing employment in the hospitality industry after graduation.